2012
DOI: 10.1007/s00441-012-1482-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porcine pCLCA2 protein during late differentiation of keratinocytes of epidermis and hair follicle inner root sheath

Abstract: Despite the discovery of the widely expressed CLCA (chloride channel regulators, calcium-activated) proteins more than 15 years ago, their seemingly diverse functions are still poorly understood. With the recent generation of porcine animal models for cystic fibrosis (CF), members of the porcine CLCA family are becoming of interest as possible modulators of the disease in the pig. Here, we characterize pCLCA2, the porcine ortholog of the human hCLCA2 and the murine mCLCA5, which are the only CLCA members expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…A recent paper revealed that CLCA2 is strongly down-regulated by UV radiation and suggested that it may play a role in epidermal differentiation and UV-dependent skin malignancies [12]. Some of the other CLCA members are also reportedly associated with epidermal differentiation [10,11]. In addition to such relationships, based on the in vitro findings of p65-induced CLCA regulation, the possible roles of NF-kB activity in vivo should be taken into consideration since some populations of keratinocytes exhibited nuclear distribution of p65 in the basal and suprabasal layers of native skin and in the organotypic culture.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent paper revealed that CLCA2 is strongly down-regulated by UV radiation and suggested that it may play a role in epidermal differentiation and UV-dependent skin malignancies [12]. Some of the other CLCA members are also reportedly associated with epidermal differentiation [10,11]. In addition to such relationships, based on the in vitro findings of p65-induced CLCA regulation, the possible roles of NF-kB activity in vivo should be taken into consideration since some populations of keratinocytes exhibited nuclear distribution of p65 in the basal and suprabasal layers of native skin and in the organotypic culture.…”
Section: Discussionmentioning
confidence: 98%
“…Human CLCA2 (hCLCA2) is localized along the basal membrane of basal epithelial cells of the cornea and skin and its expression is elevated during epithelial stratification [8,9]. Porcine CLCA2 was detected in the granular layer [10]. Among the mouse isoforms, mCLCA5 was shown to be expressed in the granular layer of the skin and oral cavity, especially in keratohyalin granules [11].…”
Section: Introductionmentioning
confidence: 97%
“…The full-length isoform was found mainly in differentiating keratinocytes, and the truncated form in basal keratinocytes. 10 The expression of mCLCA5 and its porcine orthologue, pCLCA2, were found mainly in the granular layer, 11,12 while the human orthologue, hCLCA2, was detected in basal cells. In addition, disturbance of the epidermal homeostasis by UVR caused reversed localization of the truncated CLCA2-t, to the upper cell layers, as previously observed in wounding.…”
Section: Discussionmentioning
confidence: 98%
“…9 Alternative splicing and proteolytic cleavage with subsequent secretion of the fragment(s) have complicated the analysis of the function of calcium-activated chloride channels (CLCAs). 11,12 rCLCA2 has also been shown to modulate chloride channels and transepithelial Cl À transport in salivary glands and keratinocytes. 11,12 rCLCA2 has also been shown to modulate chloride channels and transepithelial Cl À transport in salivary glands and keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation